Vasopressin receptor expression and mutation analysis in corticotropin-secreting tumors. - Dahia, P; Ahmed-Shuaib, A; Jacobs, R; Chew, S; Honegger, J; Fahlbusch, R; Besser, G; Grossman, A (1996)
Vasopressin is an important regulator of hypothalamo-pituitary-adrenal axis activation, primarily acting through the V3 receptor (V3R). Many patients with ACTH-secreting pituitary adenomas, but not normal individuals, respond to desmopressin, a relatively V2-specific vasopressin agonist, with increased ACTH and cortisol levels. We have searched for mutations of the V3R gene in ACTH-secreting pituitary adenomas and one ectopic ACTH-secreting tumor. No abnormalities were found in 12 tumors studied by PCR-single strand conformation polymorphism (PCR-SSCP) analysis. We then verified by RT-PCR whether the response to desmopressin was due to overexpression of the V3R or abnormal expression of the V2R in the pituitary tumor. We found that the V2R gene was expressed in a number of corticotroph tumors and in the ACTH-secreting ectopic tumor, and that the V3R gene appears to be overexpressed in these tumors. We conclude that V3R mutations are unlikely to be present in the ACTH-secreting tumors we examined, but that the V2R gene is expressed in the majority of the samples tested, and the V3R is expressed in all of these tumors. We speculate that the response to the desmopressin test observed in patients with Cushing's disease may be due to abnormal expression of V3R or V2R in ACTH-secreting tumors.